2005
DOI: 10.1007/s10750-004-6822-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cyanobacterial fatty acids released from Myriophyllum spicatum

Abstract: This study was carried out to identify unknown allelochemicals released from Myriophyllum spicatum and to investigate their anti-cyanobacterial effects. A series of analyses of culture solutions and methanol extracts of M. spicatum using gas chromatograph equipped with a mass selective detector revealed that M. spicatum released fatty acids, specifically, nonanoic, tetradecanoic, hexadecanoic, octadecanoic, and octadecenoic acids. Nonanoic, cis-6-octadecenoic, and cis-9-octadecenoic acids significantly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 16 publications
1
70
0
3
Order By: Relevance
“…In addition, linoleic acid also was clearly able to inhibit the growth of Phormidium tenue [22], and Selenastrum capricornutum [23]. Fatty acids are widely distributed in aquatic and terrestrial environments, indicating the possibility that fatty acids in aquatic environments may affect cyanobacterial growth [4]. In our previous works, the EC 50 of dihydroactinidiolide and β-ionone on M. aeruginosa were reported at 30.1±1.7 and 25.3±2.1 mg/L, respectively [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, linoleic acid also was clearly able to inhibit the growth of Phormidium tenue [22], and Selenastrum capricornutum [23]. Fatty acids are widely distributed in aquatic and terrestrial environments, indicating the possibility that fatty acids in aquatic environments may affect cyanobacterial growth [4]. In our previous works, the EC 50 of dihydroactinidiolide and β-ionone on M. aeruginosa were reported at 30.1±1.7 and 25.3±2.1 mg/L, respectively [24].…”
Section: Discussionmentioning
confidence: 99%
“…In aquatic ecosystems, varieties of submerged macrophytes were found to effectively inhibit the growth of blue-green algae [2]. For example, Myriophyllum spicatum [3][4][5], Vallisneria spiralis [2], Potamogeton crispus [6], Ceratophyllum demersum, and Najas marina [7] showed allelopathic effects on nuisance algae. Xian et al [2] found that six allelochemicals (2-ethyl-3-methylmaleimide, dihydroactinidiolide, 4-oxo-β-ionone, 3-hydroxy-5, 6-epoxy-β-ionone, loliolide, and 6-hydroxy-3-oxo-α-ionone) and an unknown compound from V. spiralis had strong inhibitory effects on Microcystis aeruginosa Kütz.…”
mentioning
confidence: 99%
“…Therefore, the removal of harmful cyanobacterial blooms is a crucial step for the maintenance of safe water supplies and for the safety of aquatic products [4]. Recent years have seen many studies relating to the isolation and identification of allelochemicals from aquatic plants [5][6][7][8], while the algicidal properties of terrestrial plants still get less attention [9]. Up to now, the extracts of many terrestrial plants also show inhibitory effects against cyanobacteria, such as barley straw [10][11][12][13], Chinese traditional medicines [9,14,15], and so on.…”
mentioning
confidence: 99%
“…To discuss the difference of algae growth inhibition by different fatty acids, it is essential to identify the key structures that induce such effects. Nakai et al [6] found that: (i) length of carbon chain (ii) number of unsaturated linkages (iii)positions of any double bonds may affect the anticyanobacterial activities of fatty acids. Fatty acids and polyphenols were the main allelochemicals, the inhibition mechanism had been reported in some of the literature [34][35][36][37][38][39][40][41].…”
mentioning
confidence: 99%
“…According to previous studies, N-phenyl-2-naphthylamine extracted from water hyacinth has been reported as one type of strong anti-algal allelochemical (Sun et al 1993). Nakai reported that Myriophyllum spicatum inhibited Selenastrum capricornutum and Microcystis aeruginosa coexisting in a culture (Nakai 1999), along with polyphenols (Nakai 2000) and fatty acids (Nakai 2005) from Myriophyllum spicatum exhibited growth inhibition effects. The allelopathic compound isolated from Phragmites communis, identified as ethyl 2-methylacetoacetate (EMA) (Li and Hu 2005a), showed strong inhibition activity on the growth of Chlorella pyrenoidosa and Microcystis aeruginosa (Li and Hu 2005b).…”
Section: Introductionmentioning
confidence: 99%